MODERATE ISLAMIC RELIGIOUS EDUCATION THROUGH RELIGIOUS MODERATION TRAINING FOR TEACHERS - Ihda Izzatul Hikmah; Fetty Ernawati (Universitas Muhammadiyah Surakarta, 2023)
Religious moderation is a way of looking at and behaving a person in religion in a moderate manner, namely fair and balanced, so that in understanding and practicing the teachings of religion is more concerned with a tolerant and inclusive attitude, and avoiding exaggerated and extreme behavior when implementing it. Religious moderation is not a moderated religion, but our way of religion, namely understanding and practicing a religion from a moderate perspective. Furthermore, in this study, the need for teacher training on religious moderation in schools is discussed. Because teachers are the vanguard in the learning process of religious moderation in schools. The goal is to provide additional insight and knowledge about religious moderation, as well as integrate it into learning. This research is a descriptive qualitative research using the library research method. The results of this study are that, first: the cultivation of religious moderation values has various strategies, both through policies and approaches. The effectiveness of the strategy used depends on each interrelated element. The many values of Bergama moderation have different approaches from one another. The policy of conducting training for teachers is a quite strategic approach because teachers as the vanguard in education should have insight and knowledge about religious moderation. Therefore, teachers need to gain more knowledge as a provision to integrate the values of religious moderation in schools. Second: the acquisition of steps to implement religious moderation training into a structured guide, so that the hope of gaining insight and knowledge about religious moderation can cover all the materials that are the subject of problems in the internalization of religious moderation values in schools.